ARGUMENTATION PATTERNS OF TOULMIN STUDENTS DURING ONLINE LECTURES IN THE PANDEMIC - Mohammad Archi Maulyda; Dudi Septiadi; R Radha; Anton Budiharjo; Nourma Pramestie Wulandari (Universitas Muhammadiyah Surakarta, 2021)
Student argumentation skills are considered weak during online lectures. The Toulmin Argumentation Model is an excellent model in analyzing argumentation discourse in the Science Classroom. This study aims to describe Toulmin's argumentation patterns during online lectures during the Covid-19 Pandemic. The research method used is a qualitative descriptive method. Data collection techniques used in the form of an open questionnaire. Respondents used in this study were 50 samples. The results showed that the argumentation pattern was divided into 2 categories namely, (1) Category Four Elements and (2) Category Five Elements. The Four Elements category is divided into 2 patterns, namely the C-G-W-B Pattern and the G-C-M-W Pattern. In the CGWB Pattern, the argumentation elements used are a claim (position statement), ground (data or facts), warrant (guarantee), and backing (support), while in the GCMW Pattern the argumentation elements used are ground (data or facts), claim (position statement), Capital Qualifier, and warrant. The Five Elements category forms the G-C-W-B-Pc Pattern. In the G-C-W-B-Pc Pattern, the argumentation elements used are grounds (data or facts), claims (position statements), warrant (s), backing (support), and possible rebuttal (exceptions). In the case of the five-element category, the argumentation pattern does not use a Capital qualifier